2009
DOI: 10.3168/jds.2008-1617
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of mammary metabolism and blood flow after refeeding in rats

Abstract: The production of milk is closely linked to nutritional state in many mammalian species, but the mechanisms by which changes in nutritional state are signaled to the mammary glands are poorly understood. Simultaneous measurements of mammary blood flow and glucose arterio-venous difference were made across the inguinal mammary glands of anesthetized, lactating rats. Blood flow to the mammary glands of previously fed rats was 0.48 mL/min per gram of mammary tissue. Glucose supply was 1.7 mumol/min per gram and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a meta-analysis considering 52 treatments from 24 experiments, a poor negative relationship between MP supply and mammary blood flow was observed (Lapierre et al, 2012). In lactating rats, 18 h of total feed deprivation reduced mammary blood flow 50% (Stewart et al, 2009). Refed rats recovered mammary blood flow to initial levels within 60 min.…”
Section: Mammary Blood Flowmentioning
confidence: 99%
“…In a meta-analysis considering 52 treatments from 24 experiments, a poor negative relationship between MP supply and mammary blood flow was observed (Lapierre et al, 2012). In lactating rats, 18 h of total feed deprivation reduced mammary blood flow 50% (Stewart et al, 2009). Refed rats recovered mammary blood flow to initial levels within 60 min.…”
Section: Mammary Blood Flowmentioning
confidence: 99%
“…Another study, also in rats under food restriction, observed that after 18 h without feeding, the blood flow of the left inguinal mammary artery was reduced by 48% (from 3.1 ± 0.2 to 1.5 ± 0.2 mL/min), and the glucose uptake was reduced by 88% (3.3 ± 0.4 µmol/min to 0.4 ± 0.1 µmol/min). In this study, no measurement of milk production was made [106].…”
Section: Changes In Blood Flow On Mammary Glandmentioning
confidence: 99%